Gestalt approach to solving psychosomatic problems - Kostiuchenko Олена (Psychosomatic Medicine and General Practice, 2021)
Introduction. Creation and introduction of effective psychotherapeutic means in work with psychosomatic symptoms is relevant. The aim of the study. The aim of the study: to determine the features of the Gestalt approach to solving psychosomatic problems. Research methods. Research methods: analysis of theoretical and applied aspects of the use of Gestalt techniques during practical classes with students of V.I. Vernadsky Taurida National University on the basis of surveys, questionnaires. Results and discussion. In the traditions of the Gestalt approach, a psychosomatic symptom and features of its detection are defined. A system of «design» and «dialogue» techniques has been developed in accordance with the basic Gestalt-therapeutic procedures for symptom detection, awareness of its role in life, analysis and psychological support in solving psychosomatic problems. Conclusions. The role of Gestalt techniques in dealing with psychosomatic symptoms and disorders, which will improve and enhance health, has been substantiated.